Congenital Vascular Malformations : A Comprehensive Review of Current Management - Kim, Young-Wook; Lee, Byung-Boong; Yakes, Wayne F.; Do, Young-Soo (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book is a superbly illustrated guide to the diagnosis and treatment of congenital vascular malformations (CVMs) that will enable the reader to avoid the serious pitfalls that may arise when caring for patients with this rare and complex group of lesions. After discussion of pathogenesis, classification, and differential diagnosis from vascular tumors, the clinical features of CVMs are described and illustrated, covering both the various forms (venous, arteriovenous, lymphatic, capillary, and mixed) and presentations at different anatomic sites. The current role of CT, MRI, scintigraphy, and angiography in diagnostic evaluation is explained, and treatment options, including conservative treatment, are then considered in detail. The discussion of endovascular treatment, or embolo-sclerotherapy, includes instruction on patient selection, embolic and sclerosing materials, access to the target lesion, site-specific variations in treatment strategy, and complications and their management. Indications for and performance of surgical/excisional therapy and laser therapy are also fully considered.